Adaptive Hydrodynamic Modeling for Sustainable Irrigation Management in Tidal Swamp Regions - Edwar, Raden M.; Karamma, Riswal; Maricar, Farouk; Hatta, Mukhan P. (Salehan Institute of Higher Education, 2026)
The Lalan River functions as the primary water source and plays an important role in supporting irrigation systems and water management in tidal swamp areas. However, water management in this region still faces challenges such as salinity intrusion and unstable water distribution, while conventional approaches applied have not fully considered the hydraulic characteristics and hydrodynamic conditions of the waters. This study aims to analyze the hydrodynamic characteristics of the Lalan River as the main water system in the tidal swamp irrigation area of D.I.R. Karang Agung Hilir, Banyuasin Regency, South Sumatra Province, Indonesia, in order to design an effective water management strategy for agricultural irrigation. The research methods include bathymetry, tidal, current, and salinity measurements. Hydrodynamic modeling was applied to analyze aquatic phenomena, including flow dynamics and salinity distribution patterns in tidal swamp areas. The hydrodynamic model was calibrated and validated using field data with a Root Mean Square Error (RMSE) value of 0.170 m to ensure the reliability of the simulation. The analysis results show that the application of a one-way flow system can significantly reduce salinity, from around 2–5 ppt in the old system to around 1–2 ppt during high tide and below 0.5 ppt during low tide, or a reduction of up to ±60%. This reduction allows river water to be used more effectively for agricultural irrigation. The novelty of this research lies in the adaptive hydrodynamic approach based on seasonal hydrological conditions as a foundation for designing sustainable water management systems in tidal swamp areas according to the hydrotopography of the region.